2023
DOI: 10.1136/jitc-2022-006596
|View full text |Cite
|
Sign up to set email alerts
|

CAR T-cell detection scoping review: an essential biomarker in critical need of standardization

Abstract: The expansion and persistence of chimeric antigen receptor (CAR) T-cells in patients are associated with response, toxicity, and long-term efficacy. As such, the tools used to detect CAR T-cells following infusion are fundamental for optimizing this therapeutic approach. Nevertheless, despite the critical value of this essential biomarker, there is significant variability in CAR T-cell detection methods as well as the frequency and intervals of testing. Furthermore, heterogeneity in the reporting of quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Furthermore, our finding demonstrating a positive correlation between day 5 CAR T measurement and the achievement of CR corresponds with clinical trials based on molecular methods [6,7,[34][35][36]. It is worth mentioning that previous studies, evaluating the cellular kinetics of Tisa-cel in B-cell ALL and chronic lymphocytic leukemia (CLL) transfused patients, showed that most circulating lymphocytes in the first days after infusion are CAR Ts [27]. Furthermore, the kinetics of atypical lymphocytes post-Tisa-cel (in pediatric ALL patients) had morphological changes that were distinct from other cell lineage lymphopoiesis or maturation, thus inferred to be CAR T [17].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, our finding demonstrating a positive correlation between day 5 CAR T measurement and the achievement of CR corresponds with clinical trials based on molecular methods [6,7,[34][35][36]. It is worth mentioning that previous studies, evaluating the cellular kinetics of Tisa-cel in B-cell ALL and chronic lymphocytic leukemia (CLL) transfused patients, showed that most circulating lymphocytes in the first days after infusion are CAR Ts [27]. Furthermore, the kinetics of atypical lymphocytes post-Tisa-cel (in pediatric ALL patients) had morphological changes that were distinct from other cell lineage lymphopoiesis or maturation, thus inferred to be CAR T [17].…”
Section: Discussionsupporting
confidence: 80%
“…We found a weak correlation (n = 10, r = 0.67, p = 0.034) between the time to peak of CAR Ts in the PBSs to the CAR+ cells number as measured by flow cytometry on day 7 post-transfusion. A recent review article indicated that current methodologies of CAR T cells' quantification are extremely heterogeneous and difficult to compare and standardize [27].…”
Section: Discussionmentioning
confidence: 99%
“…A good correlation of qPCR results has been shown for detection of the CAR-protein on the surface of T cells with flow cytometry [42][43][44]. In a comprehensive review of the literature from Turicek et al, the authors found that flow cytometry (used in around 43% of trials) and qPCR (used in around 57%) were the most commonly employed methods of CAR detection [45]. The authors also highlighted the need of universal approaches in detection techniques and time points as well as in the reporting of quantitative data [45].…”
Section: Car-t Cells In Aml 21 Clinical Testing Of Car-t Cells In Amlmentioning
confidence: 98%
“…In a comprehensive review of the literature from Turicek et al, the authors found that flow cytometry (used in around 43% of trials) and qPCR (used in around 57%) were the most commonly employed methods of CAR detection [45]. The authors also highlighted the need of universal approaches in detection techniques and time points as well as in the reporting of quantitative data [45]. While B-cell aplasia has been widely used to monitor the persistence of CD19-CAR-T cells, there is no such way to define "functional persistence" in AML, which necessitates the optimization of detection approaches for monitoring CAR-T cells in the blood.…”
Section: Car-t Cells In Aml 21 Clinical Testing Of Car-t Cells In Amlmentioning
confidence: 99%
“…Lack of standardization is readily apparent when considering the variety of culture systems currently used in the manufacturing process 62 . Similarly, there is heterogeneity in flow cytometric and polymerase chain reaction‐based methodologies used to detect CAR T cells post‐infusion and establish how frequently they are used 63 . However, the implementation of mass production steps seeking uniformity for therapies that are inherently examples of personalized precision medicine will represent a continuous challenge in the field 64 …”
Section: Cell Collectionsmentioning
confidence: 99%